Use of multispecies freshwater biomonitor (MFB) to assess behavioral changes of guppy poecilia reticulata and freshwater prawn macrobrachium lanchesteri in response to cadmium - M. Shuhaimi-Othman,; M. Azmah,; A.K. Ahmad, (Universiti Kebangsaan Malaysia, 2010)
The Multispecies Freshwater Biomonitor¨ (MFB) uses the measurement and analysis of different types of behaviours from different aquatic organisms for monitoring the water quality in freshwater ecosystem. The aim of this study was to determine the specific response of freshwater shrimp (Macrobrachium lanchesteri) and guppy fish (Poecilia reticulata) to cadmium (Cd) in the laboratory. Different concentrations of Cd were exposed to M. lanchesteri (1 ppb and 10 ppb) and P. reticulata (100 ppb and 560 ppb) and the behavioural changes of the organisms were recorded by MFB for 2 hours. Results showed that the behavioural and ventilation response of M. lanchesteri and P. reticulata increased with increasing exposure concentrations of Cd. Results also showed that the shrimp was more sensitive to Cd than the guppy fish and these local species were suitable as indicator organism for the MFB.